Eco Heroes in Action: Pengelolaan Sampah yang Menyenangkan di SDN 18 Ampenan - Ibrahim Ibrahim; Rosdiana Handayani; Herry Indrayati S; Alifah Nur Fitria; Aisyah Yuniza; Alivia Ayusha Putri; Atasyah Adriano (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2026)
Waste management issues in Mataram City have become increasingly urgent due to rising plastic waste volumes unmatched by public awareness, straining the environment and landfill capacity. Initial observations at SDN 18 Ampenan revealed categorized trash bins but improper sorting and minimal recycling activities, necessitating early educational interventions to foster environmental stewardship. This community service program implemented two main activities: waste sorting socialization and plastic bottle recycling practices. The socialization covered waste definitions, types, sorting methods, and benefits of recycling inorganic waste. Hands-on practices targeted Class II A and III (keychains from melted and molded bottle caps) and Class IV (flower pots from cut, decorated, and planted plastic bottles with vinca flowers), under strict supervision for safety.  Results showed high student enthusiasm, attitude shifts viewing plastic waste as valuable material, improved sorting skills, creativity, and active participation in school cleanliness. The flower pots enhanced the school garden's beauty. This program demonstrates the effectiveness of experiential learning in cultivating sustainable environmental awareness.